Silvestro Pietrsanta (1590–1647) on Ancient Coins: Symbols of Nobility and Moral Education - Czarski, Bartłomiej (Journal of Jesuit studies, 2025)
In this article, I discuss the presence of ancient coins in the works of the Jesuit scholar Silvestro Pietrasanta (1590–1647). I focus primarily on the treatise De symbolis heroicis. First, however, I present the author’s profile and review his writings. Then I discuss the relationship of ancient numismatics to emblematics and its place in the set of universal symbols. The article primarily discusses the second book of De symbolis heroicis, where Pietrasanta presents coins, mainly Roman, as carriers of individual symbols related to coats of arms and impresas. The author categorizes the coins into distinct groups based on the iconography depicted on their surface. The Jesuit scholar identifies two principal categories of monuments. The initial group evokes the past through the portrayal of a family’s progenitor or commemoration of a distinguished ancestor’s achievements. The subsequent group encompasses representations that foreshadow future events and are predominantly propagandistic in nature. Pietrasanta treats Roman coins from the republican and imperial periods separately. With regard to the latter group, he demonstrates a particular interest in the monuments associated with Christian iconography. For the author, ancient coins served as a pedagogical tool for moral education. They provide visual evidence of virtue and significant accomplishments, thereby bearing resemblance to pre-heraldic symbols.